Identifikasi Potensi Objek Wisata Alam Gua Pengkoak di Taman Hutan Raya Nuraksa: Identification Of Potency Of The Natural Tourism Object Of Pengkoak Cave In Nuraksa Forest Park - Aminah Firashinta; Irwan Mahakam Lesmono Aji; Hairil Anwar (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2021)
Pengkoak Cave is a natural tourism object located in Nuraksa Forest Park West Nusa Tenggara.